Gaps between de jure entitlements and de facto benefits: Institutional drift and non-take-up in China's maternity benefit system - Zhe Yan; Tobias ten Brink; Armin Müller (International Journal of Social Welfare, 2025)
Chinese female workers have a de jure right to maternity benefits, enshrined in law and policy since the 1950s. Using the concept of institutional drift, this article examines why entitlements are not awarded as legally stipulated. It finds that the transition from a command to a market economy undermined the effectiveness of maternity benefit entitlements. Although maternity insurance was introduced in 1994 to alleviate drift, employer non-compliance and lax enforcement resulted in non-take-up of benefits. The non-contributory design of the insurance makes employers both contributors to and distributors of the maternity benefits to which formally employed workers are entitled. Combining historical research, interviews and quantitative data, this article documents the historical evolution of maternity benefits in China, identifies drift as the mechanism underlying uneven insurance coverage and declining benefit levels, and argues that a comprehensive understanding of non-take-up must go beyond the individual worker level to include the role of employers and local governments.
Keywords: 330; employers; institutional drift; maternity benefit entitlements; non-take-up; policy implementation; social insurance